Stages of Community Empowerment Through Vocational Learning in the Micro, Small, and Medium Enterprise (MSME) of Sumber Hayati Batik Besurek Diwo, Kepahiang Regency - Citra Lorenza; Citra Dwi Palenti; Wiwin Yunita (International Journal of Innovation and Education Research, 2026)
This study aims to describe the stages of community empowerment through vocational learning at the Sumber Hayati Batik Besurek Diwo MSME, Kepahiang Regency, with a focus on three main stages: enabling, empowering, and protecting. The research method uses a descriptive qualitative approach, with data collection techniques through observation, interviews and documentation, and data validation using triangulation of sources, time, and techniques to ensure the accuracy of the findings. The results of the study show that the enabling stage is realized through the creation of a comfortable learning atmosphere indicated by the cleanliness of the learning room, the completeness of vocational learning facilities and infrastructure, and a recruitment system for students based on potential and competency certificates. The empowering stage is implemented through the provision of batik vocational learning materials, product marketing training through Instagram, Shopee, and Facebook, and strengthening business cooperation networks that encourage increased skills and self-confidence of students. Furthermore, the protective stage is achieved by implementing SOP regulations within the legal protection system through work agreements, as well as by managing production risks through the processing of rejected batik cloth into accessory products. For economic independence, preservation of the Besurek Diwo batik culture of Kepahiang Regency. Keywords: Batik Besurek Diwo, MSME, Community Empowerment, Vocational Learning